Sufistication of Social Welfare Policies in Contemporary Indonesia: Recalibrating Policy Ethics through Tasawuf-based Values - Budi Rahman Hakim; Herman L Beck (Jurnal Ilmu Sosial Indonesia (JISI), 2025)
Abstract. Indonesia’s social welfare system is structured in a very technocratic manner, adhering to legalistic frameworks that emphasize efficiency at the cost of the nation’s moral and spiritual values. This form of imbalance exacerbates governance failures, including rampant corruption, nepotism, and a decline in public trust, resulting in an ethical vacuum in the welfare policymaking process. This article presents Sufistication: a spiritually informed, void-filling framework that draws from Sufi teachings. This study, through principles of ihsan (spiritual excellence), adab (ethical comportment), and tazkiyah (inner purification), proposes an alternative model of welfare governance incorporating moral consciousness. Through conceptual analysis and Critical Discourse Analysis, this article examines policy documents, public debates, and community initiatives rooted in Sufism to show how Sufistication reinterpret welfare governance. The analysis demonstrates the ability to transcend purely instrumental rationality, granting space for spiritual intentionality and moral reflexivity, thereby recalibrating policy intent to the higher purposes of Islamic law (maqāṣid al-sharī‘ah). Sufistication relocates welfare within the framework of an ethnically constructive paradigm, thus offering responsive policy-making that is effective and infused with compassion, humanitarian.  Keywords: Sufistication, Welfare Governance, Tasawuf Value, Ethical Paradigm, Social Walfare.  Abstrak. Sistem kesejahteraan sosial di Indonesia selama ini banyak dibentuk oleh model teknokratis dan prosedural yang menekankan efisiensi serta legalitas, namun kerap mengabaikan fondasi etis dan spiritual bangsa. Ketimpangan ini telah memicu kegagalan tata kelola, seperti korupsi, patronase birokratis, dan menurunnya kepercayaan publik, sehingga tercipta kekosongan etika dalam perumusan kebijakan kesejahteraan. Artikel ini memperkenalkan konsep Sufistikasi—sebuah kerangka spiritual yang terinspirasi dari ajaran tasawuf—untuk menjawab kekosongan tersebut. Dengan mengacu pada prinsip ihsan (kesempurnaan spiritual), adab (perilaku etis), dan tazkiyah (penyucian batin), studi ini mengajukan model alternatif yang mengintegrasikan kesadaran moral dalam tata kelola kesejahteraan. Melalui analisis konseptual dan Critical Discourse Analysis, artikel ini menelaah teks kebijakan, wacana publik, dan inisiatif sosial berbasis sufistik untuk menunjukkan bagaimana Sufistikasi dapat mengarahkan kembali tata kelola kesejahteraan. Temuan penelitian menegaskan potensi konsep ini dalam menggantikan rasionalitas instrumental dengan intensionalitas spiritual dan refleksivitas moral, sehingga kebijakan selaras dengan maqāṣid al-sharī‘ah (tujuan-tujuan luhur syariat Islam). Dengan menempatkan kesejahteraan dalam paradigma yang berakar pada budaya sekaligus transformatif secara etis, Sufistikasi menawarkan jalan menuju kebijakan yang tidak hanya efisien, tetapi juga manusiawi, inklusif, dan berkelanjutan.  Kata Kunci: Sufistikasi, Tata Kelola Kesejahteraan, Nilai-Nilai Tasawuf, Paradigma Etis, Kesejahteraan Sosial.